دراسة بعض صفات بيض التفريخ عند الدجاج البلدي السوري في البيئة الساحلية تحت ظروف التربية الريفية السرحية - حميشة محسن (Latakia University Journal -Biological Sciences Series, 2019)
أجري هذا البحث كخطوة أولى ضمن مشروع بحثي للتحسين الوراثي للدجاج البلدي السوري في البيئة الساحلية. فقد درست 1281 بيضة تم جمعها من بعض القرى في محافظة اللاذقية لدراسة أهم صفات بيض التفريخ، انتخبت منها للتفريخ (865) بيضة،إذ بلغت نسبة البيض الصالح للتفريخ( 67.53%) ، وكان متوسط وزن البيضة للعينة المدروسة ككل (50.2)غ وللبيضة الصالحة للتفريخ(52.3)غ, أما متوسط دليل الشكل فكان (75.8%) وبلغت نسبة الإخصاب (89.8%) ونسبة الفقس (75%) ونسبة التفريخ(65.54%). يظهر البحث المستوى المنخفض نسبياً لقيم هذه الصفات بالمقارنة مع القيم المطلوبة للسلالات والتصالبات العالمية ومدى تأثر هذه الصفات بالعوامل البيئية والوراثية ما يشجع على وضع البرامج المستقبلية اللازمة لرفعها وتحسينها, إذ لا تعكس بواقعها الراهن المقدرات الكامنة للتراكيب الوراثية لهذا النوع المحلي. This research included 1281 eggs collected from some villages in Lattakia. The aim was to study the most important traits of incubation eggs. 865 out of total eggs were selected for incubation (67.53% were suitable for incubation). Thus, the average egg weight of the studied eggs was 50.2 gr; for incubation eggs, it was 52.3 gr. The average of the index form was 75.8%. and the percentage of the fertility was 89.8%, hatchability 75%, and chicken hatchability 65.54%. This study indicates the low level of the values of these descriptions compared with the given values which are demanded by and limited to the international breeds and crosses, and how much are they influenced by genetic and environmental factors in order to set the right future programs needed to raising and improving these values; at present, they don’t reflect the potential ability of the genetic combinations for this local kind.